An Economic Model for Assessing the Feasibility of Multilateral Wells - Abdel-Alim H. El-Sayed; M.N.J. AI-Awad; M.S. Al-Blehed; M.A. Al-Saddiqui (Journal of King Saud University: Engineering Sciences, 2001)
This paper presents an economic model developed for assessing the feasibility of drilling multilateral wells for exploiting oil reservoirs. Detailed equations are derived for calculating the cost, return on investment and discounted net present value over the production life of the oil reservoir. Equations for calculating production rate and predicting the future production performance of multilateral wells have been introduced. A comparison between horizontal well and multilateral wells is also included. A computer program has been written to perform production forecasting and economical evaluation of oil reservoirs for any given reservoir characteristics developed by multilateral wells. The model is used for choosing the best technique needed to develop oil reservoirs taking into consideration the maximum profit of the investment.